2022
DOI: 10.1016/j.toxrep.2021.12.001
|View full text |Cite
|
Sign up to set email alerts
|

High-fat western diet-consumption alters crystalline silica-induced serum adipokines, inflammatory cytokines and arterial blood flow in the F344 rat

Abstract: Highlights Silica reduced serum leptin and adiponectin, no effects on body or fat pad weight. HFWD-consumption altered pro-inflammatory cytokines in silica-exposed animals. Silica altered pulse frequency; HFWD increased mean blood flow; effects additive. HFWD affected silica-induced metabolic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 76 publications
3
14
0
Order By: Relevance
“…HFWD-consumption also increased BAL total cells, lymphocytes, neutrophils, and macrophages at 4 wk compared to the STD+AIR control cohort. These results indicate that consumption of a HFWD not only induced systemic inflammation, as shown earlier [25] , but that it also induced an inflammatory environment in the lung. We postulate that this HFWD-induced low-grade, systemic inflammation “primed” the lung and contributed to the exacerbated inflammatory response to silica dust inhalation.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…HFWD-consumption also increased BAL total cells, lymphocytes, neutrophils, and macrophages at 4 wk compared to the STD+AIR control cohort. These results indicate that consumption of a HFWD not only induced systemic inflammation, as shown earlier [25] , but that it also induced an inflammatory environment in the lung. We postulate that this HFWD-induced low-grade, systemic inflammation “primed” the lung and contributed to the exacerbated inflammatory response to silica dust inhalation.…”
Section: Discussionsupporting
confidence: 85%
“…Adiponectin has a protective role against lung injury [30] , [31] through its role of maintaining lung immune homeostasis [32] , [33] . Previously [25] , we found that, regardless of the diet consumed, silica-inhalation reduced both serum adiponectin and leptin at 8 wk in our animal model. Surprisingly, HFWD-consumption alone had lesser effects on adipokines in our animal model, which we attributed to the obesity-resistance of the F344 strain [34] .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations